Multimorbidity and health-related quality of life after tuberculosis treatment in Zimbabwe: A cross-sectional study with household comparators - Claire Jacqueline Calderwood; Edson T. Marambire; Trevor Musunzuru; Karlos Madziva; Fungai Kavenga; Eveline Muringi; Justin Dixon; Junior Mutsvangwa; Celia L. Gregson; Rashida Abbas Ferrand; Katherine Fielding; Katharina Kranzer (PLOS Global Public Health, 2026)
Chronic conditions both drive development of and are consequences of tuberculosis (TB). While there is growing awareness of chronic lung disease, data on other health conditions post-TB are limited. In this cross-sectional study in Zimbabwe, we offered adults with pulmonary TB an integrated health check at or after treatment completion, assessing uptake and yield. Members of the same households were also offered the intervention. Selecting household members without prior or current TB as a comparator, we calculated odds ratios (OR) for HIV, diabetes, hypertension, underweight, anaemia, symptoms of mental health disorders, self-reported memory difficulty, vision impairment, chronic lung disease and multimorbidity (two or more of the above); and compared health-related quality of life (HRQoL; EQ-5D value). Of 229 people with TB invited, 96 (42%) participated (median age 38 years, 54% men, median 356 days from diagnosis). Common reasons for non-participation were migration and work. Among people with TB, chronic conditions were common and, other than HIV, mostly undiagnosed. Ninety-one percent of people with recent TB had at least one chronic condition; almost two-thirds had two or more. Compared to 285 household comparators (median age 34 years, 71% female) and after adjustment for age and sex, people with recent TB were more likely to have at least one chronic condition (OR 2.30 [95% confidence interval 1.03–5.11]) but not multimorbidity (1.55 [0.86–2.78]). People with recent TB had greater odds of HIV (1.77 [1.03–3.04]), symptoms of mental health disorders (1.57 [0.96–2.56]), self-reported memory difficulty (2.13 [1.19–3.80]), impaired lung function (3.24 [1.46–7.20] among 39/92 people with TB and 155/285 household comparators with data available), and underweight (5.15 [2.28–11.61]) compared to household comparators without prior TB; hypertension was less common (0.40 [0.20–0.79]) and HRQoL was worse (p = 0.005). Uptake of chronic disease screening among people with recent TB was low, but prevalence of chronic conditions was high. Holistic approaches to treatment which identify and address these conditions are needed. The contribution of post-TB multimorbidity to morbidity and mortality among TB survivors should be included in global disease estimates. Whilst comparison to household controls aimed to reduce confounding by socio-economic status, a limitation of this approach is externality, whereby the health status of the person with TB influenced that of their household members.